Preparation of antibacterial and antifungal breathable polyether block amide/chloropropane diol membranes via solution casting. Issue 17 (8th January 2018) - Sole, Bhausaheb B.; Seshadri, Geetha; Tyagi, Ajay Kumar; Rattan, Sunita
ABSTRACT: A highly hydrophilic block copolymer polyether block amide (PEBA) is modified with chloropropane diol (CPD) to impart antibacterial and antifungal properties to it without compromising with its breathability. The antibacterial properties of modified membranes are evaluated against Staphylococcus aureus ( S. aureus, Gram positive) and Escherichia coli ( E. coli, Gram negative) bacteria by membrane culture method. CPD plays an important role in the antibacterial property with the inhibition rate reaching 99.99% for CPD modified membranes which was 27.55% and 16.82% for pristine membrane (against S. aureus and E. coli respectively) . The antifungal properties studied against Aspergllus niger, Penicillium pinophilum, Aureobasidium pullulans, Chaetomium globosum, and Trichoderma virens show heavy‐growth of fungi for pristine PEBA membrane while no growth was observed in case of CPD modified membranes. Breathability of membrane is determined in terms of water vapor transmission rate (WVTR) and it increase from 1496 g/m 2 /day to 2354 g/m 2 /day after modification. The membranes are characterized by FTIR‐ATR, SEM‐EDX, DSC, and TGA. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46097. Abstract :